(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Comparative peripheral analgesic and antipyretic activities of copper, zinc, cobalt and manganese complexes of indomethacin were studied. Peripheral analgesic effect of the complexes was evaluated by following acetic acid-induced writhing inhibition method in mice whereas antipyretic activity was assessed by Brewer’s yeastinduced pyrexia in rat model. At 10- and 20-mg/kg doses, the zinc-indomethacin complex produced significant writhing inhibition (p<0.001) by 67.35% and 77.55% whereas cobalt-indomethacin showed writhing inhibition by 61.22% and 64.63% in a dose dependent manner respectively, which were prominent compared to that of standard indomethacin (61.90% and 72.27% inhibition respectively). Moreover, the zinc-indomethacin complex exerted significant antipyretic activity at both 10- and 20-mg/kg dose by reducing body temperature from 100.38°F to 97.8°F (4th hour) and 100.36°F to 98.21°F (4th hour), respectively that were comparable to standard paracetamol. From this study, it can be said that, with further pharmacological and toxicological profiling of the zinc and cobalt complex of indomethacin, it may pave the way of discovering new drug entity. Dhaka Univ. J. Pharm. Sci. 16(2): 173-178, 2017 (December)